PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 2 KIKIM SELATAN TAHUN PELAJARAN 2019/2020 (Universitas Negeri Semarang, 2020)
The formulation of the problem in this study is the influence of the mindmapping learning model on the learning outcomes of class X students in geography in SMA 2 Kikim Selatan. This study aims to determine whether or not there is an influence of mind mapping learning models on class X student learning outcomes in geography subjects at SMA Negeri 2 Kikim Selatan. The research method used is a quantitative approach to the method of experimentation with data collection techniques obtained using observation, tests, and documentation. The average value of student learning outcomes in the experimental class can be categorized well that is 76.45 by using a mind mapping model, while the average value of learning outcomes of the control class by not using a mind mapping model can be categorized sufficiently with the average student learning outcomes is 61 , 29. Based on calculations, obtained t arithmetic> t table = 6.369> 1.683 ie t arithmetic = 6.369 and t table = 1.68 then accept the hypothesis (ha) which means